Open licensing for cultural heritage - Hamilton, Gill; Saunderson, Fred (Facet Publishing, 2017)
This practical and explanatory guide for library and cultural heritage professionals introduces and explains the use of open licences for content, data and metadata in libraries and other cultural heritage organisations.